MAGT: Multi-scale Attention Graph Transformer with Local Context Enhancement for CT Image Analysis - Qiu, Youchun (Informatica, 2025)
Computed tomography (CT) has become an important tool in cancer screening and diagnosis, where accurate image analysis can assist early detection and treatment planning. While deep learning methods have shown progress in CT image analysis, effectively capturing both local features and global context remains challenging. This paper presents MAGT, a Multi-scale Attention Graph Transformer (MAGT) framework that combines graph-based geometric modeling with transformer architectures for CT image analysis. The MAGT framework includes two main components: a Multi-Head Feature Aggregator (MHFA) that integrates features from different scales while preserving their characteristics, and a Local Context Enhancement Block (LCEB) that strengthens the capture of spatial information. This design enables MAGT to process CT images by considering both lesion characteristics and their surrounding anatomical context, similar to clinical examination procedures. The framework uses graph structures to represent spatial relationships in CT images while incorporating transformer mechanisms into model feature dependencies. Experiments conducted on four public datasets (LIDC-IDRI, LUNGx, LUNA16, and DeepLesion) demonstrate the effectiveness of MAGT; for example, on the LIDC-IDRI dataset, MAGT achieved an accuracy of 91.5% and an F1-score of 91.3%, outperforming a strong baseline (Swin-T) by 2.1% in both metrics. Ablation studies verify the contributions of different components within the framework. The results indicate that MAGT offers a practical approach for CT image analysis, potentially supporting cancer detection and diagnosis in clinical applications